MELACAK SUMBER DAN KEOTENTIKAN PENAFSIRAN MUQĀTIL BIN SULAYMĀN TENTANG AYAT KISAH PENYALIBAN DAN DIANGKATNYA NABI ‘ĪSĀ KE LANGIT - Ahmad Jauhari Umam (STAI AL-ANWAR SARANG, 2019)
This article examines the interpretation of the Qur’an about the story of the crucifixion and the lifting of the Prophet 'Īsā to the sky in Tafsīr Muqātil bin Sulaymān with a focus on the study of tracing the source of interpretation and its authenticity in surah Ᾱli Imrān verses 54-55 and surah al-Nisā' verse 157- 158. The choice of Muqātil bin Sulayman as a research subject is because he is a controversial one among the Muḥaddithīn of his doubtful credibility. In his interpretation Muqātil does not mention sanad and commentary related to history so this needs to be examined in depth. However, the superiority of Muqātil in its interpretation is that it is able to tell the story in the al-Qur'an in detail such the story of the prophet Isa. From the results of this study, it can be concluded that Muqātil bin Sulayman explained that the man crucified by the Jews was not 'Īsa but the person who was identic to him named Yahūẓā, while' Īsa was purified by Allah from the Jews by lifting him up to the sky of the earth from Bait al-Maqdis on night of Lailatu al-Qadr in Ramadhan at the age of thirty-three years. Overall Muqātil did not clearly state the sources of its interpretation, and after going through the process of tracing and muqaranah from the literature of other books, eight narrations are found.